The Endtimes of Human Rights - stephen hopgood (Cornell University Press, 2013)
Writing this book has been on my mind since Mary Robinson visited Dili in East Timor in 1999. Indonesiaâ€™s brutal occupation had recently ended. Robinson, at the time UN high commissioner for human rights, opened a two-day workshop designed to embed East Timorâ€™s pledge to uphold international human rights law. Her speech was titled â€œBuilding the Future of East Timor on a Culture of Human Rights.â€ Each of 160 participants received a kit containing all the major human rights documents and a badge that carried the words â€œHuman rights: know them, live them, defend them,â€ written in the local language, Tetun. 1 For twenty-five years, since 1975, the East Timorese had fought a guerrilla war against the Indonesian military and militias. Civilian deaths from hunger, illness, killings, and disappearances during this period are conservatively estimated at more than one hundred thousand. This was out of a population of under a million. Numerous human rights abuses were committed. 2 Somehow, led by future president Xanana GusmÃ£o, the armed Timorese resistance kept the fi ght alive as the international community made empty, rhetorical protests. Even the international human rights activists and journalists who highlighted East Timorâ€™s cause made little impact. GusmÃ£oâ€™s liberation fi ghters always seemed to me exemplary human rights defenders. What they knew was that no one else was coming to save them. Through their own tight communal bonds, shoulder-toshoulder with people on whom they depended and who in turn depended on them, they defeated a threat to their very existence. During this time, the United States continued to train some of Indonesiaâ€™s top army officers. 3 One of them, former president Suhartoâ€™s son-in-law General Prabowo, accused of masterminding systematic human rights abuses in East Timor, is now a leading candidate for the 2014 Indonesian presidential election. More than ten years after Indonesia was driven from the country, there has still been no accounting for the crimes committed under occupation.